Strengthening The Professionalism of PAUD Aisyiah Teachers in Wirogunan Village through Humanical Communication in The Era of Pandemi Covid 19 - Suyahman, Suyahman (Universitas Negeri Semarang, 2021)
This study aims to describe the strengthening of the professionalism of Aisyiah Early Childhood Education (PAUD) teachers in Wirogunan Village through humanist communication in the Covid 19 pandemic era. : qualitative descriptive research. Data collection methods: interviews with applications; Whatshaap, google form and documentation. The data analysis technique uses qualitative analysis techniques consisting of 3 stages, namely: data reduction, data display and data verification. Research result ; The results of interviews with 8 teachers and 1 principal conducted on 4-10 June 2020 obtained information: teachers are less familiar with their students, teachers have difficulty managing classes, teaching styles are monotonous, less interactive, less able to provide motivation, difficult to give examples of behavioral attitudes to students, it is difficult to educate character, less able to develop the material actually. The impact of all this is that students do not maximize their potential, interests and talents. This condition must be found a solution. One solution is to strengthen the professionalism of the Early Childhood Education (PAUD) teacher Aisyiah, Wirogunan Village, through humanist communication.